Curcumin: A Natural Product for Diabetes and its Complications - Fazel Nabavi, Seyed; Thiagarajan, Raman; Rastrelli, Luca; Daglia, Maria; Sobarzo-Sanchez, Eduardo; Alinezhad, Heshmatollah; Mohammad Nabavi, Seyed (Current Topics in Medicinal Chemistry, 2015)
Curcumin is the yellow-colored bioactive constituent of the perennial plant, Curcuma longa L., which possesses a wide range of physiological and pharmacological properties such as antioxidant, anti-inflammatory, anticancer, neuroprotective and anti-diabetic activities. Anti-diabetic activity of curcumin may be due to its potent ability to suppress oxidative stress and inflammation. Moreover, it shows a beneficial role on the diabetesinduced endothelial dysfunction and induces a down-regulation of nuclear factor-kappa B. Curcumin possesses a protective role against advanced glycation as well as collagen crosslinking and through this way, mitigates advanced glycation end products-induced complications of diabetes. Curcumin also reduces blood glucose, and the levels of glycosylated hemoglobin in diabetic rat through the regulation of polyol pathway. It also suppresses increased bone resorption through the inhibition of osteoclastogenesis and expression of the AP-1 transcription factors, c-fos and c-jun, in diabetic animals. Overall, scientific literature shows that curcumin possesses anti-diabetic effects and mitigates diabetes complications. Here we report a systematical discussion on the beneficial role of curcumin on diabetes and its complications with emphasis on its molecular mechanisms of actions.
Keywords: Curcumin